Screening of Crude Extract of Flavonoids of Moringa oleifera against Bacteria and Fungal Pathogen - Talreja*, Tamanna (Journal of Phytology, 2010)
Crude extracts were prepared from the flowers and callus ofÂ Moringa oleiferaÂ using ethanol extract and screened for their antimicrobial activity against some bacteriaÂ andfungal pathogenÂ by paper disc method. The tested gram positive bacterial strains wereÂ BacillusÂ subtilisÂ andÂ Staphylococcus aureus,Â gram negative bacterial strains wereÂ Escherichia coli, Klebsiella pneumoniaeÂ andÂ fungal pathogenÂ Candida albicans. Although flavonoids are present in all parts ofÂ Moringa oleifera,Â maximum amount was observed inÂ flowers. Hence soxhlet extract of 5 grams of powdered flowers and unorganized tissues ofÂ M. oleiferaÂ wereÂ screened for their antimicrobial activity. Among the flowers and unorganized tissue tested, the ethanol extract of callus exhibited higher antimicrobial activity when compared to the floral extract. Key words: Antimicrobial, Antifungal,Â Moringa oleifera,Â Soxhlet extract, Ethanol extract <span style="line-height: 110%; font-variant: normal !important; font-family: ";Book Antiqua";,";serif";; letter-spacing: -0.3pt; font-size: 7pt; font-weight: normal; mso-font-kerning: 0pt; mso-no-proof: no; mso-fareast-language: EN-SG; mso-ansi-language: EN-SG;" lang="EN-SG">Tamanna Talreja. Screening of Crude Extract of Flavonoids of Moringa oleifera against Bacteria and Fungal Pathogen. J Phytol 2/11 (2010) 31-35